Prognostic value of myocardial injury and chronic kidney disease in an emergency unit. (14th October 2021) - Lal-Trehan Estrada, N; Carrasquer, A; Del Moral, V; Sanchez, R; Bonet, G; Peiro, O; Fort, I; Bardaji, A
Abstract: Background: Cardiac troponin is independently associated with cardiovascular events and mortality in patients with chronic kidney disease (CKD). Their joint effect is yet to be clarified. Purpose: This study aims to evaluate the prognostic implication of myocardial injury and CKD in patients attended in an emergency room. Methods: Retrospective study carried out between January 2012 and December 2013 with consecutive patients attended in an emergency room with troponin determination, who were distributed into four cohorts according to positive troponin and/or glomerular filtration rate (GFR) <45ml/min/ 1.7. We analysed their baseline characteristics and the four-year prognosis. Results: 3622 patients were included (median age 68.5 years [IQR 55.5–79.5]; 43% were women). Compared to subjects with normal GFR, the 565 subjects with CKD were significantly older (80.5 vs 66.5 years), with worse cardiovascular profile (arterial hypertension: 87% vs 56%; diabetes mellitus: 46% vs 22%) and greater comorbidity (history of myocardial infarction: 29% vs 18%; heart failure: 17% vs 5%; peripheral vascular disease: 16% vs 5%; cerebrovascular disease: 13% vs 7%%). Myocardial injury was also related to elderly and worse cardiovascular profile and comorbidity, especially in normal GFR subjects. 23.5% (718 subjects) of normal GFR subjects presented with myocardial injury. This percentage was much higher in the presence of renal impairment (331 subjects, 58.6%). Troponin was associated with a higher risk of death (both in-hospital and during follow-up) and of readmission due to infarction or heart failure, regardless of GFR. The reference cohort in the multivariate competing risk mode was that with subjects without myocardial injury or kidney disease. This analysis showed the worst MACE (all-cause death, non-fatal myocardial infarction and heart failure admission) in four-year follow-up in patients with renal impairment and positive troponin (HR 3.94, 95% CI 3.317–4.682), second worst MACE in those with myocardial injury and with normal GFR (HR 2.408, 95% CI 2.064–2.811), and then abnormal GFR patients with negative troponin (HR 1.532, 95% CI 1.220–1.923). Patients with both myocardial injury and renal impairment had the highest mortality (HR 4.633, 95% CI 3.829–5.604) and more readmissions for heart failure (HR 2.163, 95% CI 1.647–2.841). The myocardial-injury-and-normal-GFR cohort showed significantly higher mortality than the renal-impairment-with-negative-troponin cohort (HR 2.669 vs HR 1.794), more heart failure (HR 1.951 vs 1.067) and more myocardial infarctions (HR 2.439 vs 1.235) in the follow-up. Conclusion: The results suggest that myocardial injury has better predictive power than chronic kidney disease for MACE events and also for individually mortality, readmission for heart failure or myocardial infarction. Funding Acknowledgement: Type of funding sources: None.